Engaging with geopolitical uncertainty - Mavretić, Ana (Economic and business review, 2024)
This paper studies the geopolitical riskwork practices employed by Western multinational enterprises (MNEs) in response to the Russian invasion of Ukraine, focusing specifically on divestment announcements. Using a discursive riskwork framework, the study analyses how Western MNEs articulate and legitimize their divestment decisions in a novel geopolitical context. The findings reveal that Western MNEs align their corporate actions with emerging liberal geopolitical norms and values, thereby rhetorically establishing their role as responsible geopolitical actors. The paper advances the discourse-oriented study of international business phenomena, the study of geopolitical risk management beyond adherence to sanctions and reputation management, the concept of riskwork, and the empirical studies of divestment announcements.
Keywords: international corporation; mednarodno podjetje; negotovost; Ukraine; Ukrajina; uncertainty; vojne